Human capital diversity and product innovation: A micro-level analysis - René Söllner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
The paper investigates the relationship between human capital diversity measured in terms of occupational diversity and a firm's likelihood to innovate. The empirical analysis is based on a linked employer-employee panel dataset of German firms over the period 1998 to 2007. Despite notable differences between service and manufacturing firms, our results clearly indicate a positive relationship between occupational diversity and the propensity to innovate.
Keywords: J24; L20; O31; 330; Human Capital; Diversity; Innovation; Humankapital; Qualifikation; Berufsstruktur; Innovation; Deutschland